O impacto da carga tributária na competitividade da indústria automobilística brasileira: uma análise comparativa internacional - Pinheiro, Gabriel Graeff (2025)
The Brazilian tax burden it is a known theme and widely discussed, its known that it is an obstacle for the growth of the productive sector in Brazil, and affects directly the purchasing power of the families, we could relate to Brazil Cost that it’s a set of structural, bureaucratic, logistical, and tax obstacles/barriers that impact the cost of production in the country, making Brazil one of the most expansive places to produce comparing to others. As the case of study, the Brazilian automotive sector, as we can see according to data of FIPE 2023, the taxes are 38% of the final price of popular cars in Brazil. With that on mind the search was to understand what is the actual impact of the tax burden in the competitivity of the Brazilian automotive industry, a comparative analysis with two important markets, the Mexican and the Indian, the secondary data from 1995 to 2023 showed that the Brazilian automotive industry it is losing its power in the international market, losing market in comparation to India and Mexico.